The effect of hippotherapy on gait in patients with spastic cerebral palsy - Veronika Fízková; Eva Krejčí; Zdeněk Svoboda; Milan Elfmark; Miroslav Janura (Palacky University, 2013)
BACKGROUND: Disorders of motor skills, especially regarding gait, are prevalent in nearly all forms of cerebral palsy. Through a horse’s back movement, the patient is exposed to proprioceptive stimulation, thus improvement in gait performance could be expected. OBJECTIVE: The aim of our study was to determine the effect of hippotherapy on gait in patients with spastic cerebral palsy. METHODS: Eleven subjects (age 14.3 ± 4.8 years, height 148.2 ± 17.6 cm, weight 43.3 ± 20.2 kg) with spastic cerebral palsy participated in the study. Gait assessment was performed before and after a weeklong stay. The hippotherapy was conducted daily. Kinematic data from three trials for each child was obtained using the Vicon MX system (seven infrared cameras, frequency 200 Hz). Comparison of ankle, knee, hip and pelvis movement before and after hippotherapy intervention was performed in Statistica (version 10.0) using the Wilcoxon test. To determine the effect size, Cohen’s d was used. RESULTS: After completing the short-term hippotherapy intervention, we observed a decrease in the second plantar flexion during initial swing (p < .05), decrease in knee flexion during the stance phase (p < .05), decrease in the hip range of motion in sagittal plane (p < .05) and decrease in the pelvic obliquity (p < .05). The effect size for all statistically significant differences was low. CONCLUSIONS: Hippotherapy combined with individually defined physiotherapy can lead to some changes in bipedal locomotion in terms of improvement and thus contribute to greater self-sufficiency, self-reliance and independence of patients with cerebral palsy.